Populasi Mikrob di Rizosfer dan Pertumbuhan Caisim (Brassica juncea) di Tanah Dikontaminasi Insektisida Organoklorin setelah Aplikasi Konsorsia Mikrob dan Kompos - Hindersah, Reginawanti; Rachman, Wahyuda; Fitriatin, Betty Natalie; Nursyamsi, Dedi (Jurnal Natur Indonesia, 2013)
Organochlorine insecticide hed been banned for agriculture but nowadays its residue was still found in some agriculturalsoil. One of ways to lower organochlorine residue in soil is by using degrading-organochlorine microbial consortiaaccompanied by compost application. However, application of exogenous microbes might affect bacterial and fungalpopulation in soil and hence plant growth. The pot experiment has been set up to verify the influence of Pseudomonasmallei and Trichoderma sp. and compost on total bacteria and fungi on rhizosphere of caisim (Brassica juncea L.) grownon Andisols which were contaminated with organochlorine insecticide of Heptachlor, endosulfan, dieldrin, and DDT.Experimental design was Factorial Randomized Block Design with three replicates. The first factor was microbial consortiaof P.mallei and Trichoderma sp., and the second one was the kind of compost. The result showed that effect of microbialconsortia on total bacteria population was determined by the kind of compost. Total bacterial population in rhizosphere ofcaisim grown with cow manure compost and microbial consortia was more increased. However, microbial consortia as wellas any kind of compost did not influence total fungal population in caisim rhizosphere. Amount of leaf increased due tomicrobial and compost application however plant yield did not.